Measuring the Social Impact of the Cultural and Creative Sectors: Insights from Lithuanian Experts - Lilija Kublickienė (Information & Media)
The article discusses the challenges of social impact assessment in the Cultural and Creative Sectors (CCS) in Lithuania. The varying definitions of key concepts, such as ‘cultural and creative sectors’ and ‘impact’, have led the theoretical part of the paper to focus on the clarification of these concepts, reviewing their development and the practice of application. The importance of assessing the social impact of CCS is emphasized, alongside an exploration of diverse research and measurement practices.